Praktik Tindak Pidana Gratifikasi Perspektif Sosiologi Korupsi - Amin, Muhammad Habibul; Supriyadi, Dedy; Lubis, Fauziah (Ikatan Da'i Indonesia, 2024)
This article aims to identify the phenomenon of the practice of criminal acts of gratification in administrative services using a fraud theory perspective, as well as to analyze the factors that support the development of legal culture around this practice in society. Corruption in Indonesia is a serious problem that is widespread in society. From a sociological point of view, corruption is seen as a widespread social phenomenon because of its significant impact on various aspects of life. One common example of a criminal act of corruption is the practice of gratification, where individuals provide gifts or gifts with a specific purpose. This research uses a qualitative approach with a literature review method, where the process includes comprehensive collection, analysis and interpretation of visual data narratives. The aim is to obtain a deep, comprehensive and thorough understanding of the culture of gratification practices in society from the perspective of sociological studies of corruption. The analysis of this article shows that the practice of giving gifts occurs because the person who does it feels pressure, opportunity, and reason to do so in an administrative service situation. In addition, there is also a phenomenon in society where giving gifts is considered a normal and accepted way to express gratitude to those who provide assistance.